Transcranial Direct Current Stimulation Modulates the Effect of Unreasonable Request in the Context of Peer Punishment - Pan, Jingjing; Zhu, Chengkang; Liu, Xiaoli; Wang, Yiwen; Li, Jianbiao (Frontiers in Human Neuroscience, 2019)
Making a request is a common occurrence during social interactions. In most social contexts, requesters may impose punishments and many behavioral studies have focused on the differential effects of reasonable and unreasonable requests during such interactions. However, few studies have explored whether reasonable or unreasonable requests involve differential neurocognitive mechanisms. In this study, we used transcranial direct current stimulation (tDCS) to investigate the mechanistic effects of request within the context of peer punishment. We used a modified ultimatum game (UG) task as well as a modified dictator game (DG) task. Both unreasonable and reasonable requests induced the proposer to increase their monetary offer for both tasks. Moreover, in the modified UG task, cathodal tDCS over the right dorsolateral prefrontal cortex (rDLPFC) significantly decreased the effect of an unreasonable request when compared to sham stimulation. Cathodal stimulation did not impact the effect of a reasonable request on the modified UG task. For the modified DG task, no tDCS effect for either an unreasonable or reasonable request was observed. These findings suggest that rDLPFC was only involved in decision-making processes during unreasonable requests when there was an opportunity for peer punishment. Moreover, our results indicate that reasonable and unreasonable requests involve differential neurocognitive mechanisms in the context of possible peer punishment.